161k views
2 votes
2^(-3x)=6^(x+4)
Solve for x

2 Answers

2 votes

The answer is x = - 140/39. simplify both sides then isolate the variable

User LuckyLuke
by
5.2k points
3 votes

2^- 3x = 6^x + 4

Solution: x = - 4ln(6)/ln(48) Decimal: (- 1.85137.....)

Solve For X: Step by Step:

2^(- 3x) = 6^(x + 4)

Solve Exponent:

2^-3 = 6^x + 4

log (2^-3x) = log (6^x + 4) (Take log of both sides):

( - 3x) * (log (2)) = (x + 4) * (log (6))

- 3x = (log (6)/(log (2) * (x + 4)

- 3x = 2.584963 * (x + 4)

- 3x = 2.584963x + 10.339852

Simplify both sides of the Equation:

- 3x - 2.584963x = 2.584963x + 10.339852 - 2.584963x

Subtract: 2.584963x From both sides:

- 5.584963x = 10.339852

- 5.584963x = 10.339852

- 5.584963 =====> - 5.584963

Divide both sides by: ===> - 5.584963

Hence: x ===> - 1.851373

Answer: x = - 1.851373

Hope that helps!!!!! : )

User Kaushlendra
by
5.8k points